AN INVESTIGATION ON THE LIGHTING IN JORDANIAN HOSPITALS, FOCUSING ON DAYLIGHT AND THE PREFERENCES OF THE STAFF - jaradat, Haytham; Ibrahim, Marzuki; Kassawneh, Fatema Yousef (Malaysian Journal of Public Health Medicine, 2024)
This study investigates the impact of daylighting on staff and patient well-being in Jordanian hospitals. Focusing on a government tertiary care hospital, the research employed structured interviews and questionnaires targeting various nursing professionals, ranging from junior nurses to nurse managers. Our findings reveal that access to natural light significantly enhances the comfort and mood of both patients and staff, with a notable improvement in staff work efficiency and patient recovery times. The study's results indicated that daylight plays a crucial role in hospital environments, correlating strongly with reduced stress levels and improved overall satisfaction. These outcomes emphasize the need for integrating effective daylighting strategies in hospital design to foster better health outcomes and workplace efficiency. This research contributes to the growing evidence on the importance of environmental factors in healthcare settings and offers practical insights for future hospital construction and renovation projects